The INCREASING VOCABULARY BY USING GUESSING GAME TO THE SEVENTH-GRADE STUDENTS AT SMP NEGERI 3 DAMPAL SELATAN - Arifin, Rahmatul Ummu (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Dampal Selatan, 2024)
The research was aimed to find out the lack of student vocabulary in learning English. Type of research is quantitative using a pre-experimental design one group pre test and post test. The independent variable is a guessing game. The population of research is 26 students; the sampling was total sampling technique. The results of this research show that there is an increase in students' voabulary and this can be seen from the average post-test score of 76.08, which is greater than the pre-test score of 64. Even the significance level is 0.05 and df=25, and the t-count = 8.63 and t-table = 2.06 so that we get t-count > t-table (8.63 > 2.06) which shows that students' vocabulary is significantly better after receiving treatment and the Null hypothesis (Ho) is rejected and Alternative Hypothesis (Ha) is accepted. It can be concluded that guessing games can increasing the skills of seventh-grade students at SMP Negeri 3 Dampal Selatan.